ANALISIS MANAJMEN STRATEGI DALAM MENARIK MINAT BELI KONSUMEN (Studi Pada Mini Market El-Jhon Pagar Dewa Kota Bengkulu) - Heryunda Afista; Fatimah Yunus; Kustin Hartini (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The main objective of this study is to determine the application of strategic management in attracting consumer buying interest at the El-Jhon Pagar Dewa Mini Market, Bengkulu City. This research uses a type of field research (field research), with a qualitative descriptive research method. Based on the results obtained from the research that has been done, it is known that the type of strategy that has been implemented by the El-Jhon Mini Market in attracting consumer buying interest is the first, they implement a relatively affordable and cheap price strategy. Second, from the product strategy, the products available at the El-Jhon Mini Market are complete, starting from basic necessities, household equipment, electrical equipment, baby equipment, medicines, accessories, as well as beauty and other products of good quality. Apart from that, the El-Jhon Mini Market also applies khiyar rights (with a goods return system) if there is an accidental defect at the time of purchase. The third is the distribution strategy, where the strategy is carried out by opening branches around the Bengkulu area. And fourth, the promotion strategy carried out by Mini Market El-Jhon is carried out through advertising and publicity media